Language and masculinities: performances, intersections, dislocations - Milan, Tommaso M. (Routledge, 2015)
This volume showcases cutting-edge research in the linguistic and discursive study of masculinities, comprising the first significant edited collection on language and masculinities since Johnson and Meinhof’s 1997 volume. Overall, the chapters are linked together by a critical analytical perspective that seeks to understand the relationships between discourse, masculinities, and power. Whereas some of the chapters offer detailed, linguistically informed critiques of the ways in which old and new expressions of masculinities are complicit in the reproduction of men’s hegemonic positions of power, others provide a more complex picture, one in which collusion and subversion go hand in hand. Contributions argue for the need for research on language and masculinities to expand its remit so as to engage with "gay masculinities," and unsettle gendered categories in order to consider the ways in which women, transgender, and intersex individuals also perform a variety of masculinities. Finally, unlike Johnson and Meinhof’s 1997 collection, this volume not only offers a wider—and perhaps "queerer" perspective—on the study of language and masculinities, but also covers a broader geographical and socio-cultural spectrum, including work on Brazil, Israel, New Zealand, Singapore, and South Africa.
Donné en lecture au cours LIN2685, Jones, Lucy. Masculinity in Lesbian Discourse, the Case of 'Butch' vs 'Femme', p 174-196.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; masculinité; premier cycle; queer; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques; études de genres